Lexicographic Description of a Polysemous Word in a Learner’s Dictionary Based on Its Lexical Prototype - Karasev, Anton (Lexikos, 2025)
This paper presents a practical application of the lexical prototype theory to lexicographic practice, proposing a draft model of a learner’s dictionary entry for a polysemous word based on its lexical prototype. The lexical prototype (LP) is regarded as the semantic core of a polysemous word that functions at the level of the language system and is represented in actual speech by contextual meanings: the primary meaning (PM), metonymic, and metaphorical senses. Drafting a dictionary entry based on the LP requires reconstructing the LP through analysing the contextual meanings in relation to the PM in order to establish the minimal set of semantic features that are shared by all the senses of the word. The proposed method of lexicographic description of polysemous words offers a new perspective on polysemy as a linguistic phenomenon as well as moves away from the list-based method. Keywords: lexicography, learner’s dictionary, dictionary entry, polysemy, lexical prototype, primary meaning, metonymy, metaphor, cognitive linguistics